The Importance and the Effects of the Common Commercial Policy of the European Union when Reaching Non-Economic Goals - Bokšová, Monika (2018)
This doctoral thesis analyses the role of the European Union (EU) in the international system and contributes to the ongoing debate on EU-as-a-power. Its predominant aim is to investigate the Common Commercial Policy as a tool for achieving the EU´s non-economic goals, in particular, the protection of human rights. In doing so, it offers an empirical study on how the EU´s market power is used to externalise EU human rights regulations in countries of negligible economic importance. The analysis is conducted on three different levels of policies: (1) EU Enlargement Policy, (2) EU Neighbourhood Policy and (3) other partners – economically vulnerable countries involved in the incentive arrangement General Scheme of Preferences Plus (GSP+). This is a qualitative comparative case study analysis and the two key data sets consist of a wide range of policy documents provided by the EU together with the trade agreements, and the interviews conducted with EU and member states´ representatives at various levels and in different functions. In parallel, quantitative trade-related data are used to support the arguments presented throughout the study. The analytical framework applied is thematic analysis and the patterns identified across the data are: the principle of leverage, the principle of credibility and the principle of pragmatism. This thesis demonstrates that (1) the EU does use its market power; (2) the EU externalises its human rights regulations explicitly and evidently in trade agreements across its policies; (3) the EU is a pragmatic actor and this results in policy inconsistencies and double standards; (4) the possible consequences of these inconsistencies on the EU´s credibility as an actor are taken into account by the EU.